Gangguan Stres Pasca Trauma Pada Korban Pelecehan Seksual dan Pemerkosaan - Dirgayunita, Aries (Journal An-Nafs: Kajian Penelitian Psikologi, 2016)
Sexual abuse and rape is one of the worst things that can be experienced and toughest human beings, both women and men. In addition to physical injury also brought emotional pain or psychological needs time to heal. According to WHO data in 2006 found that women abused, raped and was beaten every day around the world. At least half of the world's population who are women has experienced both physical and psychological of violence. in cases of sexual abuse and rape, mostly victims of sexual abuse and rape are women, but in some cases, men can also be victims generally performed by men as well. Perpetrators is the people around them, sometimes they know well. While most other cases, performed by people who are just been known that originally as a good man who offered to help. Sexual harassment and rapes will trigger a deep trauma to victims. Victims of rape and sexual abuse can experience stress as a result of traumatic experiences that have happened. Stress disorder endured by the victims of sexual abuse and rapes is often referred to Post Traumatic Stress Disorder (Post Traumatic Stress Disorder or PTSD).